2012 38th IEEE Photovoltaic Specialists Conference 2012
DOI: 10.1109/pvsc.2012.6317702
|View full text |Cite
|
Sign up to set email alerts
|

Antireflection and SiO<inf>2</inf> surface passivation by liquid-phase chemistry for efficient black silicon solar cells

Abstract: We report solar cells with both black Si antireflection and SiO 2 surface passivation provided by inexpensive liquid-phase chemistry, rather than by conventional vacuum-based techniques. The best cell efficiency from our first efforts was 16.4%. Nanoporous black Si antireflection on crystalline Si by aqueous etching promises low surface reflection for high photon utilization, together with lower manufacturing cost compared to vacuum-based antireflection coating. Agnanoparticle-assisted black Si etching and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Though its surface passivation effect is excellent, it requires expensive equipment, high growth temperature and a long process step. In consideration of the cost-effectiveness, liquid phase deposited (LPD) SiO 2 film [7][8][9][10] with high qualities may provide a good solution, which is also compatible with the present solar cell mass production. Yuan et al, [9] have first tried to use LPD SiO 2 film as the passivation layer of black silicon solar cells and acquired a conversion efficiency of 16.4%, showing the promising application of LPD SiO 2 film in silicon solar cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though its surface passivation effect is excellent, it requires expensive equipment, high growth temperature and a long process step. In consideration of the cost-effectiveness, liquid phase deposited (LPD) SiO 2 film [7][8][9][10] with high qualities may provide a good solution, which is also compatible with the present solar cell mass production. Yuan et al, [9] have first tried to use LPD SiO 2 film as the passivation layer of black silicon solar cells and acquired a conversion efficiency of 16.4%, showing the promising application of LPD SiO 2 film in silicon solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…In consideration of the cost-effectiveness, liquid phase deposited (LPD) SiO 2 film [7][8][9][10] with high qualities may provide a good solution, which is also compatible with the present solar cell mass production. Yuan et al, [9] have first tried to use LPD SiO 2 film as the passivation layer of black silicon solar cells and acquired a conversion efficiency of 16.4%, showing the promising application of LPD SiO 2 film in silicon solar cells. He et al, [10] have also applied LPD SiO 2 passivation layer to polycrystalline silicon solar cells, but the passivation effect and the final conversion efficiency (5.61%) are not satisfying.…”
Section: Introductionmentioning
confidence: 99%
“…Though the SiN x coating film, fabricated by PECVD technology, can reduce the surface reflectance and give a high passivation to some extent on a large amount of front surface of mc-Si solar cells for mass production, it is helpless to the passivation on the deep trench structures because it is very difficult to be deposited on such deep and narrow trenches [2,3] . It has been reported that better passivation of mc-Si solar cells surface can be obtained by coating a thin SiO 2 layer between Si and SiN x [4][5][6][7] . However, thin SiO 2 can only solve the problem of passivation and yet useless for the problem of incident light-reflection losses.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dramatically increased surface area of PS silicon might decreases the cell efficiency because of the increase of the surface recombination. One of the known technologies to solve this problem is to deposit a passivation layer, such as TiO 2 :Cr passivation layer [11] , vanadium oxide and SiO 2 [6] , into the PS structure.…”
Section: Introductionmentioning
confidence: 99%